EKSPLORASI PERAN KELEKATAN (PARENTAL ATTACHMENT) TERHADAP KEMANDIRIAN BELAJAR SISWA GENERASI ALPHA: SEBUAH STUDI LITERATUR - Gusti Ayu Nanik Ardhiani; Ni Kadek Depi Dumaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of parental attachment in fostering the learning independence of Generation Alpha students through a systematic literature review. It also identifies the factors that influence the relationship between parental attachment and learning independence and explores their implications for educational practices in the digital era. The study adopts a qualitative approach using the Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The researchers collected data from reputable academic databases, including Scopus, Google Scholar, ScienceDirect, SpringerLink, ERIC, and Indonesian journals indexed in SINTA 2–4. The initial search identified 128 articles, from which the researchers selected 15 studies that met the inclusion criteria. The researchers then analyzed these studies using thematic analysis. The findings show that secure parental attachment provides a strong psychological foundation for developing students' emotional regulation, learning motivation, self-confidence, and self-regulated learning. The review also reveals that digital technology use, parenting practices, and family digital literacy influence the relationship between parental attachment and learning independence. In addition, the study introduces the concept of digital parenting attachment as an adaptive form of emotional bonding in the digital environment. Overall, the findings demonstrate that warm and responsive emotional relationships between parents and children remain the key factor in developing the learning independence of Generation Alpha students despite the rapid advancement of digital technology.